(untitled) (Revista de História da UEG (REVHIST), 2025)
This article discusses the case of violence against "Preto João", an enslaved man who was beaten by Renovato José, a free worker, while dismantling a fence at the command of his master, Miguel José Fialho. The text is divided into two parts: the first addresses issues related to the sources; the second analyzes the slaveholding context of the city of Crato, in the Province of Ceará, during the 19th century, with an emphasis on the social practices connected to disputes among the city’s inhabitants. The main source used was the criminal case regarding the crime of bodily harm, dated 1872. The central focus of the study is to understand the processes of violence and conflict between free and enslaved workers in a city located in the southern backlands of Ceará. Keywords: Crato-CE. Violence. Backlands. Conflict. Labor.